TRADITIONAL POPULATION AND TOURISM: TAUS AS A TOOL FOR DISPUTE MANAGEMENT? - Marcondes,Daniella (2019)
Abstract The reproduction of real estate capital, generated through tourist facilities and secondary residences, is one of the main modes of production in the coastal region, causing, at times, conflicts with the interests of remnant traditional populations. This article aims to analyse the concession of the Term of Authorization for Sustainable Use (TAUS) - a land policy instrument for ownership regularization developed based on the recognition of the traditional populations’ right to housing and the management of their socioeconomic practices - to Caicara Traditional Communities, situated along Praia de Castelhanos, in Ilhabela (SP). The work was carried out by a descriptive and exploratory study, complemented by secondary data and by participant observation. It is understood that issuing the TAUS offers the caicara the power of decision and the possibility of participation; however, by its uniqueness on tourist desired territories, it appears inconsistent especially regarding the practical aspects of territorial management and disputes of these communities with external stakeholders.